Study of zinc tannates prepared with Tara powder (Caesalpinia spinosa) as anticorrosive pigments in alkyd paints and wash primer formulations - Hadzich, A. (2018)
The aim of this research was to evaluate the anticorrosive properties of alkyd paints and wash primers formulated with zinc tannates containing Tara tannins. Their inhibitory efficiency was compared with paints pigmented with well-known anticorrosive pigments by accelerated corrosion tests (salt spray test, Prohesion test, and sulphur dioxide test), natural exposure tests and some electrochemical techniques (corrosion potential, polarization resistance and impedance measurements). It was demonstrated that the capacity of inhibiting corrosion of zinc tannates is equivalent to that shown by most commercially available conventional pigments, such as zinc phosphate and zinc chromate.